Intraventricular Hemorrhage Expansion in the CLEAR III Trial: A Post Hoc Exploratory Analysis. Issue 6 (27th January 2022) - Roh, David J.; Asonye, Ifeyinwa S.; Carvalho Poyraz, Fernanda; Magid-Bernstein, Jessica R.; Joiner, Evan F.; Avadhani, Radhika; Awad, Issam; Hanley, Daniel F.; Ziai, Wendy C.; Murthy, Santosh B.
Abstract : Background: The objective of this study was to evaluate factors associated with intraventricular hemorrhage (IVH) expansion and its association with long-term outcomes. Methods: We performed a post hoc analysis of the international, multi-center CLEAR III trial (Clot Lysis: Evaluating Accelerated Resolution of Intraventricular Hemorrhage) which enrolled IVH patients between September 1, 2009, and January 31, 2015. The exposure was IVH expansion, defined as >1 mL increase in volume between baseline and stability computed tomography scans, before treatment randomization. We assessed factors associated with IVH expansion and secondarily assessed the relationship of IVH expansion with clinical outcomes: composite of death or major disability (modified Rankin Scale score, >3), and mortality alone at 6 months. The relationship of IVH expansion on ventriculoperitoneal shunt placement was additionally explored. Multivariable logistic regression was used for all analyses. Results: Of 500 IVH patients analyzed, the mean age was 59 (±11) years old, 44% were female and 135 (27%) had IVH expansion. In multivariable regression models, factors associated with IVH expansion were baseline parenchymal intracerebral hemorrhage (ICH) volume (adjusted odds ratio [OR], 1.04 per 1 mL increase [95% CI, 1.01–1.08]), presence of parenchymal hematoma expansion: >33% (adjusted OR, 6.63 [95% CI, 3.92–11.24]), time to stability head CT (adjusted OR, 0.71 per 1 hour increase [95% CI, 0.54–0.94]), and thalamic hematoma location (adjusted OR, 1.68 [95% CI, 1.01–2.79]) while additionally adjusting for age, sex, and race. In secondary analyses, IVH expansion was associated with higher odds of poor 6-month outcomes (adjusted OR, 1.84 [95% CI, 1.12–3.02]) but not mortality (OR, 1.40 [95% CI, 0.78–2.50]) after adjusting for baseline ICH volume, thalamic ICH location, age, anticoagulant use, Glasgow Coma Scale score, any withdrawal of care order, and treatment randomization arm. However, there were no relationships of IVH expansion on subsequent ventriculoperitoneal shunt placement (adjusted OR, 1.02 [95% CI, 0.58–1.80]) after adjusting for similar covariates. Conclusions: In a clinical trial cohort of patients with large IVH, acute hematoma characteristics, specifically larger parenchymal volume, hematoma expansion, and thalamic ICH location were associated with IVH expansion. Given that IVH expansion resulted in poor functional outcomes, exploration of treatment approaches to optimize hemostasis and prevent IVH expansion, particularly in patients with thalamic ICH, require further study. Registration: URL: https://www.clinicaltrials.gov ; Unique identifier: NCT00784134.